Metabolic engineering of Parageobacillus thermoglucosidasius for thermophilic production of 1-butanol - Pablo Doménech; Ivan Pogrebnyakov; Sheila Ingemann Jensen; Jasper L. S. P. Driessen; Anders Riisager; Alex Toftgaard Nielsen (AMB Express)
Abstract 1-Butanol is a promising compound for the ongoing green transition due to its potential both as a fuel and as a platform chemical, serving as a common intermediate for the bulk production of other valuable products. In this study, the thermophilic bacterium Parageobacillus thermoglucosidasius DSM 2542 was engineered to produce 1-butanol by introducing a butanol-producing pathway with thermostable enzyme variations derived from various thermophilic microorganisms. To achieve successful metabolic engineering, the relevant genes were inserted into two different chromosomal locations, employing both constitutive and inducible promoter systems. The resulting strains exhibited varying 1-butanol production depending on the promoter system used for the first half of the genes, with titres reaching up to 0.4 g/L when working under oxygen-limiting conditions. This serves as a foundation for further metabolic optimization to utilize the strain under industrial conditions.